2020
DOI: 10.3390/ijerph17093125
|View full text |Cite
|
Sign up to set email alerts
|

Combating the COVID-19 Epidemic: Experiences from Vietnam

Abstract: The COVID-19 pandemic is spreading fast globally. Vietnam's strict containment measures have significantly reduced the spread of the epidemic in the country. This was achieved through the use of emergency control measures in the epidemic areas and integration of resources from multiple sectors including health, mass media, transportation, education, public affairs, and defense. This paper reviews and shares specific measures for successful prevention and control of COVID-19 in Vietnam, which could provide usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 2 publications
1
100
1
2
Order By: Relevance
“…18 The potentially huge opportunity costs within the health sector in not responding rapidly are clearly evident. The benefits of acting early and comprehensively, like in Vietnam, 19 are a clear lesson that can be drawn from this costing exercise.…”
Section: Discussionmentioning
confidence: 99%
“…18 The potentially huge opportunity costs within the health sector in not responding rapidly are clearly evident. The benefits of acting early and comprehensively, like in Vietnam, 19 are a clear lesson that can be drawn from this costing exercise.…”
Section: Discussionmentioning
confidence: 99%
“…As being aware of challenges ahead regarding limited resources and healthcare capacities ( 31 ), the Government of Vietnam had implemented various mandatory measures in the early phase of the epidemic to “flattening the curve” ( 32 ). It is necessary for the government to have time for preparing a possible upsurge in the number of COVID-19 cases and forecasting the pandemic peak in the next stages ( 13 , 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the analysis showed that people residing in Vietnam have less stress compared to those living in Europe during Covid-19. This could be explained by the country's successful containment of the virus compared to others (Quach and Hoang, 2020;Dinh et al, 2020, Huynh, 2020Ha et al, 2020), which make their citizens feel more secured than those living in nations where the number of infected and death toll is much higher. Even though Vietnam imposes strict quarantine and social-distancing order compared to Western countries, the amazingly lower number of infected cases and death toll in Vietnam implies the undeniable effectiveness of restriction to contain the virus.…”
Section: Discussionmentioning
confidence: 99%